Molecular Modelling Analysis of the Dimerization of Acetic Acid in Non-polar Solvents - HUQ, FAZLUL (Asian Journal of Chemistry, 2010)
Molecular modelling analyses using molecular mechanics and semi-empirical calculations were carried out to investigate the dimerization of acetic acid in a vacuum and in solution in non-polar solvents such as carbon tetrachloride through hydrogen bonding. The dielectric constant of solvent was varied from 1 to 80 to change its nature from non-polar to highly polar. The results of calculation using both molecular mechanics and semi-empirical routines show that as the polarity of the solvent increases, energetically the dimeric form becomes less favourable than the monomeric form so that the equilibrium: monomer ⇔ dimer is shifted to the left. Molecular mechanics calculations based on Amber force field show that the two forms may be equally stable when the dielectric constant of the solvent lies somewhere between 2 and 3.